2022
DOI: 10.4111/icu.20210407
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy with gemcitabine and cisplatin followed by selective bladder preservation chemoradiotherapy in muscle-invasive urothelial carcinoma of bladder

Abstract: Purpose To assess the safety and efficacy of gemcitabine and cisplatin as neoadjuvant chemotherapy followed by selective bladder preservation chemoradiotherapy in muscle-invasive bladder cancer (MIBC). Materials and Methods Patients with clinical T2-T4aN0M0 MIBC eligible for radical cystectomy and cisplatin-based chemotherapy were treated with gemcitabine 1,000 mg/m 2 on days 1, 8 and 15, and cisplatin 70 mg/m 2 on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 23 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Among 30 patients with cCR after nivolumab plus NAC, 12 refused surgery but were treated with chemoradiotherapy. A possible explanation for the dropout rate is our internal protocol in which MIBC patients with a cCR after NAC could be offered bladder preservation chemoradiotherapy instead of cystectomy [16]. We found the observed DFS was impressive according to the achievement of a cCR after NAC, irrespective of subsequent therapies.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Among 30 patients with cCR after nivolumab plus NAC, 12 refused surgery but were treated with chemoradiotherapy. A possible explanation for the dropout rate is our internal protocol in which MIBC patients with a cCR after NAC could be offered bladder preservation chemoradiotherapy instead of cystectomy [16]. We found the observed DFS was impressive according to the achievement of a cCR after NAC, irrespective of subsequent therapies.…”
Section: Discussionmentioning
confidence: 74%
“…In 30 patients with a cCR, 12 refused surgery and were treated with chemoradiotherapy. Before commencing the bladder preservation chemoradiotherapy, our institutional guidelines recommended a maximal transurethral resection [16]. As a result, five of 12 patients who were treated with chemoradiotherapy had pathologic results: ypT0 (n=2), ypTis (n=2) and ypTa (n=1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although radical cystectomy was associated with better OS in patients with cT3 disease [hazard ratio 0.42, 95% confidence interval (95% CI) 0.21−0.82, P = 0.01], the study showed no significant difference in 10-year OS between the approaches (40 versus 33%, P = 0.42) in the overall population after propensity-score matching [11 ▪ ]. In a phase II study of neoadjuvant CHT with gemcitabine/cisplatin followed by selective bladder preservation chemoradiotherapy (CRT), 54 out of 138 (39.1%) patients achieved CR with 3-year metastasis-free survival reaching 65% of the cases [12 ▪ ]. Furthermore, pooled data analysis of phase II/III trials launched by the Radiation Therapy Oncology Group (RTOG) resulted in a 5-year and 10-year cancer-specific survival (CSS) of 71 and 65%, respectively, and clinical CR of 39%, almost overlapping to those achieved by radical cystectomy [13].…”
Section: Bladder-sparing Strategies: State Of the Artmentioning
confidence: 94%